Acceso al mercado chino y promoción internacional de los exportadores de puré de banano en la provincia del Oro - Bucheli Fierro, Rudy Jose (Machala : Universidad Técnica de Machala, 2025)
"This essay analyzes the opportunities and challenges faced by banana puree exporters from El Oro province in their efforts to access the Chinese market and enhance international promotion. El Oro, Ecuador’s third-largest banana-producing region, shows strong potential to diversify its offer toward value-added processed products. China is identified as a strategic destination due to its market size, sustained economic growth, and rising demand for healthy and processed foods. However, the sector encounters tariff, technical, logistical, and cultural barriers that hinder the effective participation of small and medium-sized exporters. The Ecuador-China Free Trade Agreement (FTA) presents significant opportunities by reducing tariffs and facilitating trade, yet challenges remain regarding phytosanitary certifications, sustainability standards, and technological innovation. This research, based on a qualitative and documentary approach, emphasizes the need to strengthen production capacity, improve logistics infrastructure, and foster institutional coordination. Moreover, it highlights the importance of designing tailored promotion strategies supported by certifications, international fairs, digital platforms, and public-private partnerships. The study concludes that the internationalization of banana puree requires an integral approach combining technical assistance, innovation, marketing strategies, and corporate social responsibility. Such efforts would enable exporters from El Oro to seize opportunities in the Chinese market, boost competitiveness, and contribute to regional economic development."
El ensayo analiza las oportunidades y desafíos que enfrentan los exportadores de puré de banano de la provincia de El Oro para acceder al mercado chino y fortalecer su promoción internacional. Se destaca que El Oro, tercera provincia productora de banano en Ecuador, posee un gran potencial para diversificar su oferta hacia productos procesados con valor agregado. China aparece como un destino estratégico por su tamaño, crecimiento económico y demanda de alimentos saludables. Sin embargo, el sector enfrenta barreras arancelarias, técnicas, logísticas y culturales que limitan la inserción efectiva de pequeños y medianos productores. El Tratado de Libre Comercio entre Ecuador y China abre posibilidades de expansión al reducir aranceles y facilitar el comercio, aunque persisten retos vinculados a certificaciones fitosanitarias, sostenibilidad e innovación tecnológica. La investigación, de enfoque cualitativo y diseño documental, identifica la necesidad de fortalecer la capacidad productiva, mejorar la infraestructura logística y articular esfuerzos institucionales. Además, se recomienda diseñar estrategias de promoción específicas, apoyadas en certificaciones, ferias internacionales, plataformas digitales y alianzas público-privadas. Se concluye que la internacionalización del puré de banano requiere un enfoque integral que combine asistencia técnica, innovación, estrategias de marketing y responsabilidad social. Esto permitirá a los exportadores de El Oro aprovechar las oportunidades en el mercado chino, mejorar su competitividad y contribuir al desarrollo económico regional.
Keywords: COMERCIO EXTERIOR; PURÉ DE BANANO; MERCADO CHINO; PROMOCIÓN INTERNACIONAL